2020
DOI: 10.3390/ijerph17238890
|View full text |Cite
|
Sign up to set email alerts
|

Transdisciplinary Research Priorities for Human and Planetary Health in the Context of the 2030 Agenda for Sustainable Development

Abstract: Human health and wellbeing and the health of the biosphere are inextricably linked. The state of Earth’s life-support systems, including freshwater, oceans, land, biodiversity, atmosphere, and climate, affect human health. At the same time, human activities are adversely affecting natural systems. This review paper is the outcome of an interdisciplinary workshop under the auspices of the Future Earth Health Knowledge Action Network (Health KAN). It outlines a research agenda to address cross-cutting knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 108 publications
(119 reference statements)
1
38
0
Order By: Relevance
“…Further, research is needed on specific topics to generate the evidence base that can be further tested, customized and validated during project conceptualization and policy formulation. For instance, we need an improved understanding of how climate change interacts with other environmental changes to affect health, given the potential for negative synergistic interactions [ 68 ]. Nature-based solutions is an area that is ripe for study [ 69 ] particularly for evaluating and quantifying the potential of actions to meet health objectives [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, research is needed on specific topics to generate the evidence base that can be further tested, customized and validated during project conceptualization and policy formulation. For instance, we need an improved understanding of how climate change interacts with other environmental changes to affect health, given the potential for negative synergistic interactions [ 68 ]. Nature-based solutions is an area that is ripe for study [ 69 ] particularly for evaluating and quantifying the potential of actions to meet health objectives [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional intervention has been evoked as one important tool for protecting the eyes and vision. Natural food and its derivatives play essential roles in health and wellbeing, and it has been characteristically associated with defense mechanisms against microbial agents, xenobiotics and/or physical factors, also demonstrating an immense range of health-promoting perspectives for achieving a pleasant lifespan [33,34]. Large population studies on the role of nutrition in eye health have reported controversial results over decades, mainly regarding cataracts, AMD, RD, OSD/DED, and glaucoma, and also slowing progression of the above sight-threatening diseases, by dietary interventions has also been discussed [6,8,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: State Of the Artmentioning
confidence: 99%
“…Socio-ecological production landscapes and seascapes, or Satoyama-Satoumi land-and seascapes, are considered model societies of human-nature harmony (Takeuchi et al 2016). Their multifunctional landscapes not only enhance human wellbeing and community resilience (Schippers et al 2014;Ebi et al 2020), but provide habitat for diverse flora and fauna (Takeuchi 2010). Moreover, longstanding inter-future (Takeuchi et al 2016).…”
Section: Introductionmentioning
confidence: 99%